MANAJEMEN PEMBELAJARAN PADA HOME SCHOOLING (STUDI KASUS DI HOMESCHOOLING KAK SETO SURABAYA): learning management, homeschooling - Andriani, Dwi Nila (STISOSPOL WASKITA DHARMA, 2017)
This study was conducted to describe the management of learning in homeschooling students, especially the Homeschooling Sak seto (HSKS) Surabaya. The objectives of this study were (1) to describe the lesson planning in the Homeschooling Kak Seto (HSKS) Surabaya (2) to describe the learning implementation in the Homeschooling Kak Seto (HSKS) Surabaya (3) to describe the evaluation of the students' learning outcomes in the Homeschooling Kak Seto (HSKS) Surabaya (4) Describes the relationship of Homeschooling Kak Seto (HSKS) Surabaya with parents of students related to the implementation of learning. This research uses descriptive qualitative method. Data sources obtained are data from the director of Homeschooling Kak Seto Surabaya, head tutor, and tutors who teach in Homeschooling Kak Seto (HSKS) Surabaya. While the data collection was obtained by interview method, observation, and documentation study.The result of the research shows that (1) the planning of learning in Homeschooling Kak Seto (HSKS) Surabaya choose the curriculum Kemendikbud (2) the implementation of learning in Homeschooling Kak Seto (HSKS) Surabaya divided into two programs, namely community and distance learning (3) evaluation of learning outcomes Students in Homeschooling Kak Seto (HSKS) Surabaya are from daily examination, semester exam and semester test score (4) Homeschooling institution relationship with parent, parent meeting which is held every two times in one semester. After the midterm exam and after the final exam of the semester. In addition there are home visit activities every two months, this activity is applied to students who study with distance learning program, in the process of learning parents, institutions, and learners involved.